PENGARUH KEPRIBADIAN TERHADAP KINERJA INDIVIDU : PENDEKATAN BIG-FIVE THEORY - Sri Suhandiah; Oktaviani; Ayuningtyas (Fakultas Ekonomi Universitas 45 Surabaya, 2017)
The Big Five Theory of McCrae and Costa state that personality is affected by five aspects namely Extraversion, Agreeableness, Conscientiousness, Neuroticism, and Openness to New Experience. The personality of each individual in the organization is essentialin order to achieve organization’s goal. Goal achievement is the final accumulation of individual performances in organization. This research aim to test the influence of personality based on the Big-Five Theory approach to performance, (which) mediated by organizational commitment factors. This research is explanatory research. Research testing was conducted through questioner that spread to 173 employees of Institut Bisnis dan Informatika Stikom Surabaya and used Structural Equation Model (SEM) through STATA Software for statistical tesing. The result shows that Conscientiousness and Openness to Experience are taken effect in performance, whereas Extraversion, Agreeableness, and Neuroticism are not taken effect in performance. The result of this research also finds that Organization Commitment as mediator is not affected by performance.